2015
DOI: 10.2147/ijn.s83356
|View full text |Cite
|
Sign up to set email alerts
|

Significance of postgrowth processing of ZnO nanostructures on antibacterial activity against gram-positive and gram-negative bacteria

Abstract: In this work, we highlighted the effect of surface modifications of one-dimensional (1D) ZnO nanostructures (NSs) grown by the vapor–solid mechanism on their antibacterial activity. Two sets of ZnO NSs were modified separately – one set was modified by annealing in an Ar environment, and the second set was modified in O 2 plasma. Annealing in Ar below 800°C resulted in a compressed lattice, which was due to removal of Zn interstitials and increased O vacancies. Annealing above 1,000°C ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Here, more desired functional groups are presented on the ZnO surface, which may modify its biological activity. Surface modifications of the ZnO NPs in oxidizing environments had been demonstrated to cause an important change in the antibacterial activity 69 , which can be utilized in biomaterials. For example, Galindo et al .…”
Section: Resultsmentioning
confidence: 99%
“…Here, more desired functional groups are presented on the ZnO surface, which may modify its biological activity. Surface modifications of the ZnO NPs in oxidizing environments had been demonstrated to cause an important change in the antibacterial activity 69 , which can be utilized in biomaterials. For example, Galindo et al .…”
Section: Resultsmentioning
confidence: 99%
“…The fifth method is modification by physio-chemical methods, for example, by annealing in the Ar environment at high temperatures, or plasma oxidation. With that, the effects of modification can be different: Ar annealing decreases the antibacterial activity of ZnO nanoparticles, while plasma oxidation improves antibacterial properties of ZnO nanoparticles against E. coli and S. aureus [120]. The sixth method is the use of additives causing photocatalysis of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have suggested that electrostatic interactions are not the unique mechanism responsible for the antibacterial activity of nano-ZnO. The surface defects of nano-ZnO, such as corner defects, edge defects, and chemical defects, have a significant effect on the antibacterial activity that induces cell wall mechanical damage [ 113 , 114 ]. In the same way, the morphology of nano-ZnO also causes physical damage to bacteria [ 65 ].…”
Section: Antimicrobial Activity Of Nano-zno Modified Ti Implantsmentioning
confidence: 99%